Una anàlisi comparativa del coneixement de català de l'alumnat castellanoparlant autòcton i l'alumnat hispà en finalitzar l'educació infantil a Catalunya - Vila, Ignasi; Oller, Judith; Fresquet, Montserrat (Caplletra. Revista Internacional de Filologia, 2008)
In Catalonia, in a short period of time, statistics have raised from the 1% recorded ten years ago to the current 13% of students of foreign’s origin. This change has increased linguistic diversity regarding student’s background. However, more thana 50% are from Hispanic origin and the majority have Spanish as their mother tongue. In this case, and strictly from a linguistic point of view, the linguistic immersion programs used in Catalonia to teach Catalan to Spanish students maintain their validity. The article compares Catalan learning in two Spanish-speaking populations of 253 and 157 pupils of autochthonous and foreign origin at the end of childhood education. Results indicate that differences between both populations are related tofamily factors such as the mother’s educational level, individual ones, time spent in Catalonia, and scholar factors, such as percentage of allophone students in their classroom.